Reducing thermal damage to adjacent normal tissue with dual thermo-responsive polymer via thermo-induced phase transition for precise photothermal theranosis. (August 2022) - Wang, Rui; Wang, Xu; Mu, Xueluer; Feng, Wenbi; Lu, Yingxi; Yu, Weisong; Zhou, Xianfeng
Abstract: Photothermal therapy has been extensively studied to improve the light-to-heat efficiency for tumor ablation, but could cause severe damage to adjacent healthy tissue due to the thermal transfer, the random distribution of photothermal agents (PTAs), or combination hereof. Herein, we solve this dilemma with a material design strategy to develop a P(AAm- co -AN)- b -P(NIPAM- co -DMAa)- b -P(AAm- co -AN) ABA triblock copolymer by RAFT polymerization, which exhibits both UCST and LCST dual thermo-responsive behaviors in aqueous solution. The P(AAm- co -AN) block with appropriate AN content allows to finely tune its UCST to ∼ 43°C, which can effectively co-assemble with camptothecin (CPT) and Cy7-TCF, a near-infrared (NIR) PTA, realizing the photo-activated "on-demand" release of CPT and Cy7-TCF. The LCST of P(NIPAM- co -DMAa) segment is adjusted to ∼ 53°C by varying DMAa content, enabling an irreversible sol-to-gel transition. The heat transfer in hydrogel and heat dissipation at the interface of hydrogel-adjacent tissue are limited, resulting in selectively cell killing in tumor, with little hyperthermia in adjacent tissues. Moreover, the hydrogel continues to release CPT to enhance the synergistic efficacy of PTT with chemotherapy. These results suggest that dual thermo-responsive polymer can contribute PTT with high selectivity and negligible side effects for precise medicine. Statement of Significance: Photothermal therapy exploits the susceptibility of tumor cells toward external light-induced hyperthermia, but can cause severe damage to adjacent healthy tissue due to thermal transfer, random distribution of photothermal agents (PTAs), or combination hereof. Here, we solve this dilemma by developing a P(AAm- co -AN)- b -P(NIPAM- co -DMAa)- b -P(AAm- co -AN) triblock copolymer with UCST and LCST dual thermo-responsive behaviors, realizing the sequential micelle-unimer-hydrogel phase transitions. The polymer can effectively encapsulate PTA/drug, achieve long systemic circulation, accumulate in tumor through EPR effect, regulate drug release by controlling tumor temperature above UCST via irradiation, and finally exhibit a sol-gel transition, eradicating the heat transfer to adjacent tissue. This represents a practicable strategy to guide the design of next-generation polymeric vector that can contribute PTT with negligible side effects. Graphical abstract: Image, graphical abstract